2014
DOI: 10.1002/14651858.cd008953.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for speech disorder in Friedreich ataxia and other hereditary ataxia syndromes

Abstract: Treatment for speech disorder in Friedreich ataxia and other hereditary ataxia syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 60 publications
1
14
0
1
Order By: Relevance
“…glycopyrrhonium, trihexyphenidyl) and fluoxetine 7,12 may ameliorate drooling, although they were not included in a recent Cochrane Review on treatment options in hereditary ataxias. 151 Injections of botulinum neurotoxin may be considered if drooling persists after conservative treatment. 152 Videofluoroscopic swallowing studies may be useful to detect silent aspiration; 98 however, one should try to avoid this diagnostic tool to minimize exposure to ionizing radiation.…”
Section: Evidence-and Expert-based Recommendationsmentioning
confidence: 99%
“…glycopyrrhonium, trihexyphenidyl) and fluoxetine 7,12 may ameliorate drooling, although they were not included in a recent Cochrane Review on treatment options in hereditary ataxias. 151 Injections of botulinum neurotoxin may be considered if drooling persists after conservative treatment. 152 Videofluoroscopic swallowing studies may be useful to detect silent aspiration; 98 however, one should try to avoid this diagnostic tool to minimize exposure to ionizing radiation.…”
Section: Evidence-and Expert-based Recommendationsmentioning
confidence: 99%
“…In a recent survey by Ataxia UK [2], people with progressive ataxia identified speech and communication problems as one of the top three most troublesome symptoms of their disease with significant negative impact on their lives. Whilst our understanding of the nature of the communication problems experienced by these patients has improved significantly over time [3][4][5][6][7][8][9][10][11][12][13], a Cochrane Review on treatment efficacy for progressive ataxia syndromes concluded that "there is insufficient and low or very low quality evidence from either RCTs or observational studies to determine the effectiveness of any treatment for speech disorder" (Vogel et al, p. 1 [14]). Clinicians are therefore currently unsure of how to deal with ataxic dysarthria.…”
Section: Introductionmentioning
confidence: 99%
“…In IDE-treated FA patients, generally, a reduction in oxidative stress markers was reported and many patients showed an improvement of non-neurological symptoms, as well. However, in a subsequent randomized, double-blind, placebo-controlled trial, no statistically significant difference between the placebo and IDE was revealed on the International Cooperative Ataxia Rating Scale [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%